Induced defense response in small cardamom plants by Bacillus subtilis strain Bs against capsule rot pathogen, Phytophthora meadii - M Murugan, G Sivakumar, M K Dhanya, (Journal of Spices and Aromatic Crops, 2015)
The objective of this study was to investigate the mechanism by which Bacillus strains confer plant protection. Bacillus subtilis strain Bs was identified as potential bacterial antagonist against cardamom capsule rot pathogen, Phytophthora meadii. This strain was tested for its ability to induce defense related enzymes viz., peroxidase (PO), polyphenoloxidase (PPO) and total phenols against P. meadii in cardamom plants. Cardamom plants treated with bacterial antagonist and challenge inoculated with P. meadii showed higher levels of defense related enzymes and phenols compared to antagonist alone, pathogen alone and untreated plants. B. subtilis strain Bs induced higher activities of total phenols (182 μg g-1 of tissue), PO (2.81 change in OD min-1 g-1 of tissue) and PPO activity (1.01 change in OD min-1 g-1) in cardamom plants treated with P. meadii. The present study clearly indicated that the bacterial antagonist B. subtilis has the ability to induce defense related enzymes in cardamom plants against P. meadii.